Bandiera Official's Promotional Strategy to Encourage Environmentally Conscious Fashion Consumers: Strategi Promosi Bandiera Official untuk Mendorong Konsumen Fashion yang Peduli Lingkungan - Mohammad Dwi Fajar Romadhon Dwi Fajar; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Rapid fast-fashion cycles frequently trigger overproduction and environmental degradation in the garment sector. Specific Background Bandiera Official addresses these market challenges by integrating sustainable practices, modular designs, and digital marketing techniques. Knowledge Gap However, practical frameworks combining eco-friendly material transitions with structured promotional and supply chain strategies in fashion SMEs remain understudied. Aims This study analyzes strategic solutions for overproduction, eco-conscious material adoption, social media engagement, and discount management. Results Findings indicate that combining pre-production market research, organic materials, tailored discount structures, and targeted influencer collaborations optimizes operational efficiency and brand loyalty. Novelty This research provides an integrative framework linking eco-conscious fashion operations with direct digital promotional channels for emerging brands. Implications The proposed approach offers fashion entrepreneurs actionable guidance to achieve sustainable growth and strong competitive positioning. Keywordspromotion strategy; environmentally conscious; sustainable fashion; digital marketing; inventory management. Key Findings Highlights Modular designs and pre-production research mitigate overproduction and deadstock issues. Organic material adoption combined with supplier evaluation supports eco-friendly manufacturing goals. Strategic referral discounts and influencer collaborations strengthen social engagement without compromising margins. Keywords: Promotion Strategy, Environmentally Conscious, Sustainable Fashion, Digital Marketing, Inventory Management